Utilizing agricultural waste in brick manufacturing for sustainable consumption and circular economy - Muhammad Salman Ahmad; Muhammad Nauman Ahmad; Tufail Muhammad; Muhammad Jalal Khan; Farwa Jabbir; Saleh A. Alghamdi; Majid Alhomrani; Abdulhakeem S. Alamri; Shahen Shah (Scientific Reports)
Abstract The construction industry in South Asia, heavily reliant on coal-fired brick kilns, significantly contributes to environmental pollution, impacting public health and agricultural productivity. In Pakistan, brick kilns consume over 50% of the nation’s coal, often using low-quality coal and waste materials that emit harmful pollutants such as CO, SO2, particulate matter (PM), and hydrogen fluoride (HF). This study explores sustainable brick production by incorporating agricultural by-products, specifically the invasive weed Parthenium hysterophorus L., as an additive to clay. The integration of 15–20% Parthenium biomass by weight resulted in bricks with enhanced porosity (up to 64% at 50% biomass addition) and reduced density, lowering energy consumption during firing by approximately 15–20% while maintaining compressive strength within acceptable limits (15–20 MPa). Additionally, this approach reduced HF emissions by over 50% during the firing process, mitigating adverse effects on nearby vegetation. Conversations with 50 brick kiln owners in Peshawar revealed enthusiasm for adopting this method, contingent on cost reductions (potentially 10–15% lower production costs) and government-supported pilot projects. This research aligns with UN Sustainable Development Goals (SDGs) for sustainable cities (SDG 11), responsible consumption (SDG 12), and climate action (SDG 13), promoting a circular green economy. Policy interventions, including subsidies, training workshops, and awareness campaigns, are recommended to facilitate adoption, benefiting local communities and the environment. Future studies should investigate the scalability and adaptability of this approach across diverse regions and manufacturing sectors.